Communicative functions of syntactically indivisible utterance «Good» (based on the material of the Slavic languages): - - Latushka, Hanna P. (Journal of the Belarusian State University. Philology, 2019)
Communicative functions of syntactically indivisible utterance Good in the Belarusian, Ukrainian, Czech and Bulgarian languages were considered. The classification of agreement was created and the groups of agreement that include Good (for example, hurried agreement, agreement with reassurance, approval, agreement with doubt, etc.) were described. Syntactically indivisible utterance Good together with alternants and semantic equivalents was presented. Contexts of usage Good based on the material of dramaturgic works were adduced also. The features of Good usage in each of the analyzed language were described. Conclusions about similarity and differences of Good functioning in the Slavic languages were made, polyfunctionality of utterance was demonstrated. The results of the work were summarized in the table which represent syntactically indivisible utterance Good, its alternants and the groups of agreement in which they were detected for each of the analyzed language.